Attitude, intention, and consumer behaviour of millennial generation toward location-based SMS advertising - Yoga, I Made Sindhu; Paramartha, I Gusti Ngurah Darma (International research journal of management, IT and social sciences, 2018)
The aim of this study is to ascertain the attitude, intention and consumer behaviour of millennial generation toward the implementation of marketing communication by using Short Message Service (SMS) technology according to consumer location. In current technological developments, the promotion strategy, particularly advertising, has adapted through various digital marketing media. Mobile marketing, one of them is SMS Advertising still used by various companies in order to increase potential consumer awareness as the first step to trial product and encourage the purchases. Several previous researches discovered that most consumer attitude toward the SMS advertising tend to be negative. Moreover, SMS with Location-based advertising service disturb consumer privacy. This study tries to see the indicators which can be optimized to develop attitudes, intention and positive behaviours and the affordable effort as suggestion that the advertisements can be delivered by SMS with location-based advertising services and more effective to get attention and accepted by consumers of millennial generation.